2005
DOI: 10.2320/matertrans.46.2067
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Directionally Solidified B<SUB>4</SUB>C&ndash;TiB<SUB>2</SUB>&ndash;SiC Ternary Eutectic Composites by a Floating Zone Method and Their Properties

Abstract: Directionally solidified B 4 C-TiB 2 -SiC composites were prepared by a floating zone method using B 4 C, TiB 2 and SiC as starting materials. The B 4 C-TiB 2 -SiC system was ternary eutectic whose eutectic composition was 51.2B 4 C-8.1TiB 2 -40.7SiC (mol%). The ternary eutectic composite showed a lamellar microstructure where B 4 C(104), TiB 2 (100) and SiC(111) planes were perpendicular to the growth direction. The Vickers hardness of the B 4 C-TiB 2 -SiC ternary eutectic composite was 28 to 32 GPa. The elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
(23 reference statements)
2
13
0
3
Order By: Relevance
“…Some promising results have been reported for the B 4 C-SiC, B 4 C-TiB 2 and B 4 CTiB 2 -SiC eutectic composites. [18][19][20] However, the study on the TiC-TiB 2 -SiC eutectic composite has not been reported. In this study, the TiC-TiB 2 -SiC ternary composites were prepared by arc-melting, and the microstructure, hardness, thermal conductivity and electrical conductivity were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Some promising results have been reported for the B 4 C-SiC, B 4 C-TiB 2 and B 4 CTiB 2 -SiC eutectic composites. [18][19][20] However, the study on the TiC-TiB 2 -SiC eutectic composite has not been reported. In this study, the TiC-TiB 2 -SiC ternary composites were prepared by arc-melting, and the microstructure, hardness, thermal conductivity and electrical conductivity were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A melt-solidification process is another route to synthesize fully dense composites. We have preciously prepared several carbide-boride composites by arc melting and floating zone melting, and investigated the microstructure and some characters of B 4 C-SiC, 15) TiB 2 -SiC, 16) B 4 CTiB 2 -SiC 17) and TiC-TiB 2 -SiC 18), 19) eutectic composites. Since the eutectic composites have a self-assembled lamellar or rod-like microstructure with a highly coherent interface, they would have a highly thermally stable microstructure and high mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Both SiC [110 WÁ(KÁm) À1 ] and TiB 2 [80 WÁ(KÁm) À1 ] have relatively large thermal conductivities at room temperature. 114,115 The thermal conductivity generally follows rules of mixing; however, in Fig. As shown in Fig.…”
Section: (3) Electrical and Thermal Propertiesmentioning
confidence: 99%
“…39,114-116 Therefore, thermal conductivity at various temperatures has been investigated in B 4 C-TiB 2 , B 4 C-SiC, and B 4 C-TiB 2 -SiC ternary DSEs produced via FZ method by Gunjishima et al 39,114 and Li et al, 115 respectively. Both SiC [110 WÁ(KÁm) À1 ] and TiB 2 [80 WÁ(KÁm) À1 ] have relatively large thermal conductivities at room temperature.…”
Section: (3) Electrical and Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation